Modulated illumination microscopy: application perspectives in nuclear nanostructure analysis - Cremer, Christoph; Schock, Florian; Failla, Antonio Virgilio; Birk, Udo J. (Journal of microscopy, 2024)
The structure of the cell nucleus of higher organisms has become a major topic of advanced light microscopy. So far, a variety of methods have been applied, including confocal laser scanning fluorescence microscopy, 4Pi, STED and localisation microscopy approaches, as well as different types of patterned illumination microscopy, modulated either laterally (in the object plane) or axially (along the optical axis). Based on our experience, we discuss here some application perspectives of Modulated Illumination Microscopy (MIM) and its combination with single-molecule localisation microscopy (SMLM). For example, spatially modulated illumination microscopy/SMI (illumination modulation along the optical axis) has been used to determine the axial extension (size) of small, optically isolated fluorescent objects between ≤ 200 nm and ≥ 40 nm diameter with a precision down to the few nm range; it also allows the axial positioning of such structures down to the 1 nm scale; combined with laterally structured illumination/SIM, a 3D localisation precision of ≤1 nm is expected using fluorescence yields typical for SMLM applications. Together with the nanosizing capability of SMI, this can be used to analyse macromolecular nuclear complexes with a resolution approaching that of cryoelectron microscopy.
Gesehen am 05.08.2024
Publikationsdatum: 15. April 2024 (Online)